اجتاهات الكتاابت األكادميية والرسائل العلمية يف اجلامعات املاليزية اليت تناولت موضوع األيتام ورعايتهم وأبرز مشكالهتم - Fahad Mohamed N. Alshemmeri,; Fadlan Mohd Othman,; Mohd Farhan Md Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Kingdom of Saudi Arabia has taken care of the interests of orphans, as evidenced by the establishment of Al-Issa Chair for Orphan Research based at Umm Al-Qura University. The Chair has sought to gather information on orphans in terms of management, interests, challenges, improvements, etc. This includes consideration of what Malaysia has done in caring for orphans through research written on orphans in all respects. This article aims to analyze the numerical and qualitative characteristics of theses in universities and academic writings conducted on orphans in Malaysia. The second objective is to identify research trends in the fields of orphans in Malaysia. The third objective is to identify the specialties that produce the most scientific theses about orphans. This study adopts the desk approach, especially the survey method. Information was collected through the collection of data on the subject from scientific sources. The data was then analyzed using the descriptive method based on the research trends and aspects studied. The most important findings of the research are that the project has a great benefit to the Kingdom of Saudi Arabia through the comparison between Malaysia and Saudi Arabia in the field of orphan care. Among the axes around which the National Transformation Program revolves is to improve the level of living services provided to individuals, private and non-profit institutions by improving the system of social services, health care and safety levels, raising the attractiveness of the labor market and enabling segments of society to participate in it. Also, the interest in studying the problems of the orphans and proposing solutions to these problems through solid and reliable scientific research has a great impact on improving the level of social services for orphans and rehabilitating them in a way that makes them good citizens, and enables them to contribute to advancing development in the Kingdom.